Identification and Control of Combustible Dust Hazards - Paul Amyotte; Mohammad Alauddin; Chris Cloney; Christina Clarke; Kayleigh Rayner Brown (Chemical Engineering Transactions)
This paper describes application of a Plan/Do/Check/Act training scheme to the identification of combustible dust hazards and the prevention and mitigation of combustible dust fire and explosion risks. The geographical focus of the research is the eastern Canadian province of Nova Scotia. It was determined that over the 20-year period from 2003 – 2023, wood, paper, and grain processing industries contributed significantly to the data base of combustible dust incidents (in addition to several coal mine explosions in prior years). This finding, along with the results of a combustible dust regulatory analysis, formed the basis for development of eight training modules and three one-page guidesheets centred on the fundamental rights of frontline workers to know about hazards, participate in hazard remediation, and refuse work with unacceptable risk – all in relation to combustible dusts.